LINGVOPOETIC ASPEKTS OF SHADOW THEORY IN ARTISTIC THINKING (SCIENCE TIME JOURNAL, 2026)
The article aims to uncover the roots of the spiritual world that can be identified through fiction. The category of flame and shadow theory were discovered. The article seeks to convey to others the attributes of new views in the study of the most important aspect of art hermeneutics - the essence of art. It shows the hitherto unknown aspect of art, the aspects that open up in the process of understanding it. The article gives an idea of the viability and innovation of the elements of realism reflected in the works of European realism literature of the XIX century. Feedback is strengthened by the example of a number of exemplary works.  The article is devoted to covering the problems of the hermeneutic research of artistic works in a new way today. The article analyzes the main problems of hermeneutic method of new rakurs poetic issues. The article analyzes the principles of social and political factors in the creation of art poetic language and hermeneutic analisis of the text in uzbek classic lyrics.  The article shows the bases of analysis of etymological aspects of dictionary units widely used in samples of Uzbek classical literature in the method of gerbarism.